Biochemical methane potential of sheep manure: Focus in pathogen removal - Beily, María Eugenia; Morici, Gabriel Edgardo; Crespo, Diana Elvira; Schapiro, Javier Hernan (International Organization of Scientific Research, 2019)
Biochemical methane potential (BMP) test is a useful laboratory-scale tool to determine the biodegradability and methane potential from different manure. The aims of this study were to evaluate the BMP of sheep manure and the elimination of pathogens after going through anaerobic digestion. The BMP was carried out in mesophilic temperature (35ºC) with a substrate/inoculum (S/I) ratio of 0.5 gSV/grSV At the beginning and in the end of the experiment the following variables were determined, pH, total and soluble chemical oxygen demand (CODT and CODs respectively), total ammonia nitrogen (TAN), free ammonia nitrogen (FAN), volatile fatty acid (VFA), partial and total alkalinity (PA and TA, respectively), total coliforms, faecal coliforms, Escherichia coli, Salmonella spp. and gastrointestinal nematodes (GIN) eggs. Methane and carbon dioxide contents in the biogas were measured using gas chromatography. The results showed a specific methane production of 0.12 LCH4 / gSVad and a CODS removal of 67%. No presence of faecal coliforms, E.coli and GIN eggs was detected. The BMP test demonstrated that mesophilic anaerobic digestion is a viable option to reduce organic and pathogenic load in sheep manure.